Determination of major phenolic compounds in apples: Part I-Optimization of high-performance liquid chromatography separation with diode array detection - Sklenářová, Hana; Bílková, Aneta; Pechová, Martina; Chocholouš, Petr (Journal of separation science, 2018)
The separation of seven phenolic compounds including gallic acid, chlorogenic acid, epicatechin, quercitrin, rutin, phloridzin, and phloretin present in apple peel and pulp and differing in elution properties has been optimized using high-performance liquid chromatography with diode array detection. Several stationary phases were tested to achieve the efficient separation of phenolic compounds in fruit extracts and C18 was found to be the most efficient. Core-shell and fully porous C18 packings were assessed with respect to the complex composition of the fruit extracts. The developed high-performance liquid chromatography method comprised gradient elution in which mobile phase A was water at pH 2.8 adjusted with acetic acid and B was acetonitrile. The gradient shape was the following: 0 min 95% A/5% B, 2.5 min 85% A/15% B, 12 min 50% A/50% B, 15 min 95% A/5% B. The flow rate was 1 mL/min, injection volume 10 μL, and UV detection at 255, 280, 320, and 365 nm was applied. Our method was validated for both C18 core-shell and fully porous packings. The resolution 6.2-14.8, symmetry 0.99-1.34, peak capacity 18-60, peak area repeatability 0.45-1.00% relative standard deviation, calibration range 0.125-5 mg/mL (0.25-10 mg/mL for chlorogenic acid and rutin), correlation coefficients of calibration curve 0.9976-0.9997, and accuracy evaluated as recovery 95.56-107.54% were determined for the core-shell column.
Keywords: fenoly; Phenols; vysokoúčinná kapalinová chromatografie; Chromatography, High Pressure Liquid; Malus